Transformasi Digital Islam di Kota Jambi : Kajian terhadap Orientasi Baru Pembelajaran Berbasis Teknologi - Jamrizal, Jamrizal; Bafadhal, Izhar (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The rapid advancement of digital technology has significantly impacted the education sector, including Islamic education in Jambi City. Islamic institutions have gradually integrated digital platforms to support teaching and learning processes, leading to more flexible and interactive ways of delivering religious content. This study aims to explore how new orientations in technology-based learning are being implemented in Islamic education within the socio-cultural context of Jambi. Using a qualitative descriptive approach and library research method, data were collected from relevant scientific literature, government documents, and digital publications. The findings reveal a clear transformation from traditional to digital Islamic learning models, characterized by the use of online platforms, multimedia content, and social media-based religious education. Teachers have adopted the role of digital facilitators, while students have become more active and independent learners. Despite notable challenges such as limited access to technology and low digital literacy, the integration of digital tools has opened up opportunities for creative, contextual, and inclusive Islamic education. This research contributes to the theoretical understanding of digital transformation in religious education and offers practical insights into developing localized digital learning strategies rooted in Islamic values and cultural identity.